Effect of styrylpyrone derivative (SPD) and SPD/foscarnet combination towards virus infected cell - Nazlina, Ibrahim; Saleha, Shahar; Noor Zarina, Abdul Wahab; Norefrina Shafinaz, Md. Nor (2019)
A styrylpyrone derivative (SPD) known as goniothalamin is a compound isolated from Goniothalamus umbrosus. Herein, we showed SPD inhibition of human herpes virus type-1 (HHV-1) infection. In addition, the possible mechanism of anti-HHV-1 activity was proposed through a combination treatment between SPD and commercial antiherpetic drug, Foscarnet (PFA).